The impact of kineziological treatment of plyometric type in the development of motor and specific motor skills in handball - Kelmendi, Diellza Shaqiri; Selimi, Musa; Miftari, Florian (Journal of Education, Health and Sport, 2018)
The survey includes a total of 30 young- junior handball players from the Municipality of Gjilan, Kosovo. Handball Club "Drita" is used as an experimental group and the Handball Club "Zhegra" as a controlling group. The assessment of basic and specific motoric skills of the experimental group was done in two time periods, first one before kinesiological treatment and after the kinesiological treatment with plyometric exercises as an additional program with 2 exercises per week. The purpose of this research was to validate the impact of the 3 months training process with plyometric exercises, on some motoric and specific motoric variables responsible for achieving success in the handball game. The sample of variables is composed of 9 basic motoric variables and 2 specific motoric variables. The t-test for the dependent variable shows that the differences gained in all motoric and specific variables after kinezoiologic treatment with plyometric exercises (besides variables running at 30 meters from the high start and foot taping) are statistically significant. The results obtained after their processing show that kineziologic treatment with additional plyometric exercises has influenced the increase of basic and specific motoric skills.